PERAN QRIS DALAM MEMAJUKAN USAHA MINUMAN MATCHA DI WISMA 46 BNI - Alvin Tan; Henny (Jurnal Serina Abdimas, 2026)
This article aims to introduce and implement the Indonesian Standard Quick Response Code (QRIS) in advancing Micro, Small, and Medium Enterprises (MSMEs) in the beverage sector, particularly in the PKM matcha beverage business. E-wallets have become the main payment method for MSMEs besides cash. The ease and convenience of using e-wallets make them the choice of the people. QRIS is presented as a standardization solution that simplifies various digital payment methods. The implementation of QRIS in matcha beverage businesses is expected to overcome traditional operational challenges, such as difficulties in finding change, the risk of counterfeit money, and manual transaction recording. The implementation method used is descriptive, explaining the role and procedures for using QRIS. In addition to the direct impact on transactions, QRIS integration also indirectly contributes to increased financial inclusion for MSME players. Analysis of QRIS transaction data also allows matcha business owners to understand consumer purchasing patterns, facilitating more accurate decision-making regarding marketing strategies and inventory management. The presence of QRIS has opened the door for matcha MSMEs to fully adapt to the digital ecosystem. Overall, QRIS acts as an essential catalyst for digitalization, not only as a payment tool, but also as an instrument to increase the productivity, profitability, and competitiveness of matcha beverage MSMEs in the midst of the digital economy era. The recommendation put forward is the importance of continuous socialization and education regarding digital financial management to maximize the benefits of QRIS implementation. Artikel ini bertujuan untuk mengenalkan dan mengimplementasikan Quick Response Code Indonesian Standard (QRIS) dalam memajukan Usaha Mikro, Kecil, dan Menengah (UMKM) di sektor minuman, khususnya dalam kegiatan PKM usaha minuman matcha. E-wallet telah menjadi model pembayaran utama selain tunai bagi UMKM. Kemudahan dan kenyamanan menggunakan e-wallet menjadikannya pilihan masyarakat. QRIS hadir sebagai solusi standarisasi yang menyederhanakan berbagai metode pembayaran digital. Implementasi QRIS pada usaha minuman matcha diharapkan mampu mengatasi tantangan operasional tradisional, seperti kesulitan mencari uang kembalian, risiko uang palsu, dan pencatatan transaksi manual. Metode pelaksanaan yang digunakan adalah deskriptif dengan menjelaskan peran dan tata cara penggunaan QRIS. Selain dampak langsung pada transaksi, integrasi QRIS juga secara tidak langsung berkontribusi pada peningkatan inklusi keuangan bagi pelaku UMKM. Analisis data transaksi QRIS juga memungkinkan pemilik usaha matcha untuk memahami pola pembelian konsumen, memfasilitasi pengambilan keputusan yang lebih tepat terkait strategi pemasaran dan manajemen inventaris. Kehadiran QRIS telah membuka pintu bagi UMKM matcha untuk beradaptasi penuh dalam ekosistem digital. Secara keseluruhan, QRIS berperan sebagai katalisator digitalisasi yang esensial, tidak hanya sekadar alat pembayaran, tetapi juga sebagai instrumen untuk meningkatkan produktivitas, profitabilitas, dan daya saing UMKM minuman matcha di tengah era ekonomi digital. Rekomendasi yang diajukan adalah pentingnya sosialisasi dan edukasi berkelanjutan mengenai manajemen keuangan digital untuk memaksimalkan manfaat dari implementasi QRIS.